Migration and the ECtHR - Berkes , Lilla (The ECHR at 70: The Central European Narrative, 2025)
European Court of Human Rights. The ECtHR's migration practice began to flourish in the early 1990s, in the context of expulsion and detention. Following the Soeringen and Abdulaziz cases, the Court rapidly adopted new and new expectations of States Parties, in particular in the wake of the refugee crisis of the 2010s. As a result of the Court's law-enforcement activities, States cannot be relieved of their legal obligations, particularly their human rights obligations, simply because they (in their view) act against a migrant outside their territory. They must now also be extremely careful when it comes to return, because they are also responsible for the practices and circumstances of the third country to which they return the applicant. A number of decisions have also been taken in relation to shorter and longer periods of detention, closed or semi-closed regimes. It cannot be ignored, however, that this tendency is counteracted by the need for sovereignty on the part of states. The study thus first points out the relationship between migration and sovereignty, and then presents the role of the ECtHR in human rights law and in the assessment of migration in general. As the ECtHR's practice has now become extremely diverse, the study focuses on border-related cases, with a focus on extraterritorial excision, border procedures, summary returns, indirect refoulement as current and challenging issues for the Eastern European states. Keywords: migration, ECtHR, sovereignty, transit zones, asylum, territorial excision